Efektivitas Kebijakan Merger Bank Syariah Indonesia (BSI) dalam Revitalisasi Pembangunan Ekonomi Berbasis Syariah - Rahim, Wahida; Supardin, Ikhlas; Gasali, Ikhsan (el hisbah Journal of Islamic Economic Law, 2025)
Indonesia as a country with a majority Muslim population has an urgency to develop a sharia-based economic system as a just alternative in facing conventional economic dynamics. This study aims to analyze the effectiveness of the merger policy of Bank Syariah Indonesia (BSI) in supporting the strategy of revitalizing economic development based on sharia principles and improving community welfare. The method used is normative qualitative research with a social approach and descriptive analysis of secondary data in the form of regulations, institutional documents, and academic publications on Islamic economics. The results of the study show that BSI as a combination of three state-owned Islamic banks is not only able to strengthen the national sharia economic structure, but also become a motor for digital transformation, strengthening human resources, and financial inclusion for middle-to-lower business actors. Thus, BSI's merger policy can be declared effective. This research contributes to the development of an Islamic economic development model that is oriented towards the benefit of the ummah and emphasizes the importance of collaboration between the state, financial institutions, and society in realizing welfare based on sharia values.